Gender Differences in Characteristics and Outcome in Primary Intraventricular Hemorrhage - Guo, Rui; Yin, Lu; Chen, Ruiqi; Zhou, Liang; You, Chao; Ma, Lu; Li, Hao (Current Neurovascular Research, 2019)
Background: Primary intraventricular hemorrhage (PIVH) is a rare type of Intracerebral Hemorrhage (ICH), which is poorly understood. This study aimed to investigate gender differences in patients' characteristics, management and outcome at discharge and 90 days after PIVH. Methods: Consecutive patients with PIVH from a single center in China were enrolled over a 7- year period. Gender differences in demographics, risk factors, etiological subtypes, treatment, and outcomes were examined. The logistic regression models were used in the study to identify the predictors of poor outcome. Results: In total, 174 patients were analyzed, and 77 (44.3%) of them were women. Women with PIVH were younger (p = 0.047), with lower systolic and diastolic blood pressure (p = 0.02 and p = 0.004, respectively). They had more cases caused by Moyamoya disease (p = 0.038). There were fewer patients with hypertension (p = 0.008), smoking (p<0.001), chronic alcoholism (p<0.001), harbored lower hemoglobin (p<0.001) and Absolute Monocyte Count (AMC) (p = 0.04) at admission compared with men. There were no differences between female and male patients regarding the mortality and poor outcome in the multivariable-adjusted models ((OR = 0.57; 95% CI, 0.15-2.14) and (OR = 0.86; 95% CI, 0.32-2.37), respectively). In subgroup analysis after adjustment, the gender specific independent predictors for unfavorable outcome were higher with a Graeb score (OR = 1.78; 95% CI, 1.01-3.13) or AMC (OR = 9.66; 95% CI, 1.20-12.87) in women, and lower Glasgow coma scale (GCS) score (OR = 0.64; 95% CI, 0.47-0.87) or acute hydrocephalus (OR = 0.17; 95% CI, 0.03-0.86) in men. Conclusion: Women with PIVH exhibit some distinctive baseline features compared with men. The gender difference of the PIVH does not appear to affect the neurological outcome. The predictors of poor outcomes are Graeb score and AMC in women and GCS score and acute hydrocephalus in men.
Keywords: Intracerebral Hemorrhage (ICH)